Identification of Protease Producing Halophilic Bacteria from Bledug KuwuMud Volcano - Muhammad Saifur Rohman; Irfan Dwidya Prijambada; Yohanna Anisa Indriyani; Heri Hendrosatriyo (Indonesian Journal of Biotechnology, 2012)
The objective of this research was to isolate and identify the halophilic bacteria from Bledug Kuwu-mudvolacano having an ability to produce proteolytic enzyme. From this work, 6 bacterial isolates were obtainedfrom mud and water samples using artificial sea water media after incubation at room temperature. Threeout of the 6 isolates (BKL-3, BKL-5, and BKA-1) were selected for further analysis. BKL-3, BKL-5 and BKA-1exhibited an ability to grow at salt concentration greater than 10%. BKL-3 could grow on media supplementedwith 15% of salt, meanwhile BKL-5 and BKA-1 could grow at 20% of salt, respectively. Furthermore, thoseisolates also exhibited proteolytic activity when they were grown on casein media. The phylogenetic analysisbased on the 16SrRNA gene sequences showed that the BKL-3 belong to the group of Bacillaceae, whilst BKL-5and BKA-1 isolates were relatively distance from the group of Halomonadaceae. Therefore, BKL-5 and BKA-1could be considered as the allegedly new species that were separated from Halomonadaceae